2021
DOI: 10.3390/cancers13153703
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Chemoradiotherapy versus Radical Hysterectomy Followed by Tailored Adjuvant Therapy in Women with Early-Stage Cervical Cancer Presenting with Pelvic Lymph Node Metastasis on Pretreatment Evaluation: A Propensity Score Matching Analysis

Abstract: To compare the oncologic outcomes between chemoradiotherapy (CRT) and radical hysterectomy followed by tailored adjuvant therapy in patients with early cervical cancer presenting with pelvic lymph node metastasis. We retrospectively analyzed the medical records of women with early cervical cancer presenting with positive pelvic nodes identified on pretreatment imaging assessment. Propensity score matching was employed to control for the heterogeneity between two groups according to confounding factors. Overall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…There was some studies on this issue.Lijie Cao et al [12]conducted a retrospective study involving 861 cases of cervical squamous cell carcinoma with lymph node metastasis,with 85 patients received no adjuvant treatment, 283 patients treated with radiotherapy, and 493 patients with concurrent chemoradiotherapy(CCRT).They concluded that adjuvant radiotherapy or CCRT was not associated with a survival bene t compared to surgery with no adjuvant treatment. Some studies, however, had a different view.Takashi Shibutani et al [13] conducted a study involving 69 squamous cell cervical cancer with lymph node metastases.They recommend avoiding RH as primary treatment for those patients and CCRT should be considered.A single-center, retrospective study conducted by Jongmoo Park et al [14]reached similar conclusions.For cervical cancer patients with pelvic lymph node metastases, more studies focused on the treatment of postoperative adjuvant therapy,because these studies were conducted before the FIGO 2018 staging system was published. At present, the treatment strategies for patients with FIGO 2018 stage IIIC1 cervical cancer are inconclusive and few studies have been conducted, and there is no discussion on adenocarcinoma.In 2021, Shuko Miyahara et al [15] conducted a study of 92 patients with stage IIB-IVA cervical cancer who received radical radiotherapy.…”
Section: Data Ltering Processmentioning
confidence: 62%
“…There was some studies on this issue.Lijie Cao et al [12]conducted a retrospective study involving 861 cases of cervical squamous cell carcinoma with lymph node metastasis,with 85 patients received no adjuvant treatment, 283 patients treated with radiotherapy, and 493 patients with concurrent chemoradiotherapy(CCRT).They concluded that adjuvant radiotherapy or CCRT was not associated with a survival bene t compared to surgery with no adjuvant treatment. Some studies, however, had a different view.Takashi Shibutani et al [13] conducted a study involving 69 squamous cell cervical cancer with lymph node metastases.They recommend avoiding RH as primary treatment for those patients and CCRT should be considered.A single-center, retrospective study conducted by Jongmoo Park et al [14]reached similar conclusions.For cervical cancer patients with pelvic lymph node metastases, more studies focused on the treatment of postoperative adjuvant therapy,because these studies were conducted before the FIGO 2018 staging system was published. At present, the treatment strategies for patients with FIGO 2018 stage IIIC1 cervical cancer are inconclusive and few studies have been conducted, and there is no discussion on adenocarcinoma.In 2021, Shuko Miyahara et al [15] conducted a study of 92 patients with stage IIB-IVA cervical cancer who received radical radiotherapy.…”
Section: Data Ltering Processmentioning
confidence: 62%
“… 41 Park et al found no differences in the oncologic outcomes between CCRT and radical hysterectomy followed by tailored adjuvant therapy in patients with early cervical cancer presenting with pelvic LNM; however, 88.7% of patients required adjuvant radiotherapy after surgery, these findings suggest that CCRT can avoid unplanned tri-modality therapy without compromising oncologic outcomes. 42 Standard radiation therapy fields for cervical cancer include the whole pelvis, external iliac, internal iliac, and presacral LNs. 43 Compared with standard radiation therapy, highly conformal therapy, such as IMRT, has the potential to reduce radiation-induced toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al found no differences in the oncologic outcomes between CCRT and radical hysterectomy followed by tailored adjuvant therapy in patients with early cervical cancer; however, 88.7% of patients required adjuvant radiotherapy after surgery. These findings suggest that CCRT can avoid unplanned trimodality therapy without compromising oncologic outcomes [ 26 ]. In the present study, 70.2% of patients in the PST group and 77.4% in the NAC + RS group required postoperative radiotherapy or chemoradiotherapy, which need the patients return multiple times to the hospital for treatment.…”
Section: Discussionmentioning
confidence: 99%